Instagram as Social Media and His Role in The Tourism Promotion - Santoso, Aprih; Sulistyawati, Ardiani Ika; Vydia, Vensy (Indonesian Journal of Business and Entrepreneurship, 2022)
The Covid-19 pandemic has brought significant changes in all fields, including the tourism sector. This qualitative descriptive study aims to describe tourism promotion through Instagram social media in the city of Semarang. This research is a qualitative descriptive study. Since the research was still ongoing during the Covid-19 pandemic, the research was carried out using an online system using the Questionnaire and Interview instrument which was also conducted online through the WA application. The informants are Instagram account admins, Instagram social media users, academics in the tourism sector, and travel agencies that use Instagram social media as a promotional medium. The result of the research is that tourism promotion in Semarang City through Instagram social media is carried out by designing content, determining platforms, designing programs, program applications, and monitoring and evaluation. Keywords: promotion, Instagram, tourism, content, covid